A study on the application of hybrid propulsion system of small size fishing vessels in South Korea. (2nd October 2022) - Hwang, Junyoung; Kim, Jongsu; Jeon, Hyeonmin; Kim, Seongwan
ABSTRACT: In order to respond to strengthened environmental regulations, research on various eco-friendly technologies is actively underway in each industry. In particular, in the shipping sector, goals are set and regulations are strengthened step by step to reduce air pollutant emissions by ships. About 62% of the ships registered in South Korea are registered as fishing boats, of which 32% are aged for more than 21 years. Aging fishing boats are the main culprits of reducing fuel consumption efficiency and emitting air pollutants due to poor performance of the institution. In addition, the burden on fishermen is expected to increase as the South Korean government pushes to join the Trans-Pacific Partnership, which includes a ban on fisheries subsidies. Therefore, in this study, a target ship was designated and the operation pattern of the ship was analyzed to examine the feasibility of applying the engine-electric hybrid propulsion system to reduce air pollutant emissions from ships and increase fuel consumption efficiency.